2007
DOI: 10.1377/hlthaff.26.1.238
|View full text |Cite
|
Sign up to set email alerts
|

Quality Of Care For Acute Myocardial Infarction At Urban Safety-Net Hospitals

Abstract: Safety-net hospitals are experiencing increasing financial strains, possibly affecting their quality of care. We compare quality at safety-net and non-safety-net urban hospitals for Medicare beneficiaries admitted with acute myocardial infarction (AMI). Although safety-net hospitals had modestly higher risk-standardized thirty-day all-cause mortality rates and modestly lower adherence to quality-of-care performance measures than nonsafety-net hospitals, there was much heterogeneity among safety-net hospitals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 11 publications
(6 reference statements)
2
58
0
1
Order By: Relevance
“…6 Despite the financial challenges faced by safety nets, there is strong evidence indicating that safety net providers can and do provide care that is comparable to, and in some cases better than, that available from private sources. [7][8][9][10] If the care provided to the populations in safety net settings reduces health care disparities, closures in the safety net system will further exacerbate this severe problem. Ensuring their continued success represents a component of the overall solution to the problem of disparities in health care for ethnic minorities.…”
Section: Introductionmentioning
confidence: 99%
“…6 Despite the financial challenges faced by safety nets, there is strong evidence indicating that safety net providers can and do provide care that is comparable to, and in some cases better than, that available from private sources. [7][8][9][10] If the care provided to the populations in safety net settings reduces health care disparities, closures in the safety net system will further exacerbate this severe problem. Ensuring their continued success represents a component of the overall solution to the problem of disparities in health care for ethnic minorities.…”
Section: Introductionmentioning
confidence: 99%
“…Despite national reductions in AMI mortality rates in the past decade (3), 30-day risk-standardized mortality rates (RSMRs) for patients hospitalized with AMI vary as much as 2-fold between the highest and lowest hospitals (1). Previous studies have identified hospital volume (4,5), urban location (6), teaching status (1, 7), geographic region (1,8,9), safety net status (10), and patient socioeconomic status (11) as correlates of AMI mortality rates. However, even together, these factors leave much of the variation in RSMRs unexplained (11), and they are also not readily modifiable.…”
mentioning
confidence: 99%
“…These include geographic region, 70-72 hospital volume, 73,74 urban location, 75 teaching status, 72,76 and safety net status. 77 Variation in outcome does not seem to associate with large differences in protocols or processes of care, such as rapid response teams, clinical guidelines, use of hospitalists, and medication checks. 78 Instead, hospitals in the top or bottom tier of risk-standardized mortality after myocardial infarction differ substantially in terms of their organizational goals and values, senior management involvement, staff presence and expertise in care for patients with acute myocardial infarction, communication and coordination among relevant groups, and problem solving and learning.…”
Section: A Public Health Approach To Cardiac Arrestmentioning
confidence: 98%